Cryotherapy versus CO2 laser in the treatment of plantar warts: a randomized controlled trial - Nahid Hemmatian Boroujeni; Farhad Handjani (Mattioli1885, 2018)
Background: Warts are one of the most common infections in humans. Plantar warts are a subtype of non-genital warts, and several procedures and topical treatments have been used in its treatment. Cryotherapy is one of the most popular modalities, but it is time-consuming and remission rates vary in different studies. CO2 laser was the first laser used for treating warts. To date, no clinical trial has been done to compare CO2 laser with cryotherapy in the treatment of plantar warts. Patients and Methods: This randomized controlled trial was performed in order to compare the efficacy and number of sessions needed to treat plantar warts in 60 patients who had received no previous treatment in the previous 3 months. They were randomly allocated to the cryotherapy or CO2 laser group. The number of sessions needed for response and the recurrence rate after a 3-month follow-up was compared in the 2 groups.   Results: Sixty patients with plantar warts were randomly allocated to either the CO2 laser or cryotherapy groups. Median age was 25 (range=18-53) and 27 (range= 18-75) years in the cryotherapy group and CO2 laser groups, respectively. Both groups were matched for age and sex (56% male and 44% female in the cryotherapy group and 34% male and 66% female in the CO2 laser group). The median number of sessions needed for complete resolution of the warts in the CO2 laser and cryotherapy groups were 1 (range=1-2) and 3 (range=1-12), respectively. The difference in the number of sessions was statistically significant between the 2 groups (P-value≤0.001). Recurrence rates after a 3-month follow-up was not statistically significant (P-value= 0.069). Conclusion: The number of sessions needed to treat plantar warts was less using CO2 laser than cryotherapy; therefore, this modality can be a good addition to the already existing anti-wart armamentarium.